2014
DOI: 10.5901/mjss.2014.v5n4p135
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leadership Styles on Employee Organisational Commitment in Higher Learning Institutions

Abstract: The current study seeks to determine the impact of leadership styles on employees '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
4
16
0
1
Order By: Relevance
“…This style pays attention to his or her employees, thereby stimulating and inspiring them to accomplish unprecedented results, which goes beyond the stated expectations, and the leaders are able to develop their capacity. These findings are in line with previous studies done in this regard by Abasilim et al (2018a), Dariush et al (2016), Garg and Ramjee (2013), Mert et al (2010), Othman et al (2013), Wiza and Hlanganipai (2014), Yahchouchi (2009), andAbasilim et al (2018b) who stated that transformational leadership style relates more with employees' commitment and recommended that this style of leadership should be developed by leaders of organizations. This implies that attention should be paid to training leaders on transformational leadership skills to achieve desirable employees' commitment.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This style pays attention to his or her employees, thereby stimulating and inspiring them to accomplish unprecedented results, which goes beyond the stated expectations, and the leaders are able to develop their capacity. These findings are in line with previous studies done in this regard by Abasilim et al (2018a), Dariush et al (2016), Garg and Ramjee (2013), Mert et al (2010), Othman et al (2013), Wiza and Hlanganipai (2014), Yahchouchi (2009), andAbasilim et al (2018b) who stated that transformational leadership style relates more with employees' commitment and recommended that this style of leadership should be developed by leaders of organizations. This implies that attention should be paid to training leaders on transformational leadership skills to achieve desirable employees' commitment.…”
Section: Resultssupporting
confidence: 91%
“…Studies carried out by scholars so far have reported only on the relationship between leadership styles and employees' commitment in other sectors and countries (Dahie et al, 2017;Dariush et al, 2016;Garg & Ramjee, 2013;Gcaza et al, 2018;Mulugeta & Hailemariam, 2018;Wiza & Hlanganipai, 2014;Yahchouchi, 2009) with limited studies done within the Nigerian work context and in specific terms the Civil Service Commission in Nigeria (Abasilim et al, 2018a(Abasilim et al, , 2018bFasola et al, 2013;Okonkwo et al, 2015;Othman et al, 2013). Although these studies have contributed to the understanding of the relationship that exists between leadership styles and employees' commitment, there is a gap as to whether the outcomes of previous studies hold sway in Nigeria and also the influence of demographic variables on the relationship between leadership styles and employees' commitment.…”
Section: Research Problemmentioning
confidence: 99%
“…Wiza & Hlanganipai, 2014;Clinebell et al, 2013;Felfe et al, 2010;Castro et al, 2008), which suggest that leadership can foster the development of an emotional attachment to the organization on followers. This attachment can be undertaken conveying a motivational vision, as an expression of an idealized picture based on organizational values and culture (Bass & Avolio, 1993).…”
Section: Enhancing Affective Commitment Through Leadershipmentioning
confidence: 99%
“…More elevated amount of passionate knowledge drives workers towards arrangement with association's objectives and goals. Wiza & Hlanganipai (2014) The study uncovered that transformational organization style has a basic and positive relationship with loaded with feeling and term delegate obligation while transactional activity style has vital and positive relationship with simply institutionalizing obligation. In view of the discoveries of the examination, it is significant that authority styles assume an essential part to an employees` authoritative duty and it is vital for hierarchical strategy creators to think about this with a specific end goal to meet authoritative objectives.…”
Section: Literature Reviewmentioning
confidence: 95%